2020
DOI: 10.1590/pboci.2020.026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Untreated Dental Caries among Primary School Children: A Cross-Sectional Study

Abstract: To evaluate the dental caries experience and clinical consequences of untreated dental caries (UDC) among primary school children of Al Jouf region, Saudi Arabia and to determine the correlation between dental caries experience and clinical consequences of UDC. Material and Methods: A 250 primary school children 6-7 years were recruited using systematic random sampling. The prevalence of dental caries in deciduous dentition was assessed by following WHO criteria using the dmft index and the clinical consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Data for primary and permanent dentitions was extracted and tabulated in Table 1 , Table 2 , respectively. Seven articles included both primary and permanent teeth ( Madhan et al, 2021 , Aqeeli et al, 2021 , Gudipaneni et al, 2021 , Al-Badr et al, 2021 , Al-Samadani et al, 2017 , Farooqi et al, 2015 , Bhayat et al, 2013 ), while ten studies only reported caries in primary teeth ( Alamri et al, 2017 , Vanka et al, 2022 ; AlMarshad et al, 2021a , AlMarshad et al, 2021b ; Gudipaneni et al, 2020 , Al-Malik et al, 2019 , Alhabdan et al, 2018 , Abdallah et al, 2016 , Al-Meedani and Al-Dlaigan, 2016 , Alkarimi et al, 2014 ). Sixteen articles reported caries in permanent teeth ( Alsaif et al, 2022 , Al-Zahrani et al, 2022 , Alghamdi et al, 2022 , Gudipaneni et al, 2022 , Alotaibi et al, 2021 , Al-Ansari and Nazir, 2020 , Abdellatif and Hebbal, 2020 , Abolfotouh et al, 2020 , Basheer et al, 2020 , Alshahrani et al, 2018 , Aljanakh, 2017 , Alkhadra, 2017 , Mustafa et al, 2016 , Al-Shahrani et al, 2015 , Bhayat and Ahmad, 2014 , Togoo et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data for primary and permanent dentitions was extracted and tabulated in Table 1 , Table 2 , respectively. Seven articles included both primary and permanent teeth ( Madhan et al, 2021 , Aqeeli et al, 2021 , Gudipaneni et al, 2021 , Al-Badr et al, 2021 , Al-Samadani et al, 2017 , Farooqi et al, 2015 , Bhayat et al, 2013 ), while ten studies only reported caries in primary teeth ( Alamri et al, 2017 , Vanka et al, 2022 ; AlMarshad et al, 2021a , AlMarshad et al, 2021b ; Gudipaneni et al, 2020 , Al-Malik et al, 2019 , Alhabdan et al, 2018 , Abdallah et al, 2016 , Al-Meedani and Al-Dlaigan, 2016 , Alkarimi et al, 2014 ). Sixteen articles reported caries in permanent teeth ( Alsaif et al, 2022 , Al-Zahrani et al, 2022 , Alghamdi et al, 2022 , Gudipaneni et al, 2022 , Alotaibi et al, 2021 , Al-Ansari and Nazir, 2020 , Abdellatif and Hebbal, 2020 , Abolfotouh et al, 2020 , Basheer et al, 2020 , Alshahrani et al, 2018 , Aljanakh, 2017 , Alkhadra, 2017 , Mustafa et al, 2016 , Al-Shahrani et al, 2015 , Bhayat and Ahmad, 2014 , Togoo et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini sesuai dengan penelitian Gudipaneni, dimana ia menemukan skor indeks DMFT pada perempuan lebih tinggi yaitu 6,35 dan laki-laki 5,37. 9 Penelitian Dewi juga menunjukkan hal yang berbeda dimana skor DMFT pada perempuan lebih tinggi yaitu 3 sementara pada laki-laki 2,7. Pada anak perempuan erupsi gigi terjadi lebih cepat 1-6 bulan dibandingkan dengan anak laki-laki pada usia kronologis yang sama, sehingga gigi berkontak dengan faktor penyebab karies lebih lama.…”
Section: Pembahasanunclassified
“…In addition to studying the OHP associated with tooth decay, the clinical consequences of UDC associated with poor OHP should be investigated. The northern province of the KSA has a high prevalence of UDC and its clinical consequences in preschool children (Gudipaneni, 2019 ; Gudipaneni et al, 2019 ). Therefore, the present study aims to evaluate the prevalence of UDC and its clinical consequences associated with OHP.…”
Section: Introductionmentioning
confidence: 99%